CONVERTING A SLEEVE GASTRECTOMY INTO ROUX-EN-Y GASTRIC BYPASS AFTER GASTRIC FISTULA - Nogueiro, Jorge (2024)
Sleeve Gastrectomy (SG) is the most widely performed bariatric surgery worldwide. Despite being considered a relatively simple surgery compared with other metabolic choices, it has no negligible risk of postoperative complications. Gastric fistulas are one of the most feared complications and the most consensual explanation is the increased intraluminal pressure because of any cause of gastric emptying impairment. Due to its complex nature and multifactorial origin, the treatment is challenging and usually involves clinical, endoscopic and surgical management. To date, there is no consensus about the treatment or the ideal time for treating gastric fistulas after SG, but conversion to RYGB remains one of the options to solve this issue mainly as it can decrease the intraluminal pressure of the gastric tube. We aim to present a video of a laparoscopic conversion to RYGB in a patient with gastric fistula after SG.